2016
DOI: 10.3758/s13414-016-1186-4
|View full text |Cite
|
Sign up to set email alerts
|

Two-year-olds’ sensitivity to subphonemic mismatch during online spoken word recognition

Abstract: Sensitivity to noncontrastive subphonemic detail plays an important role in adult speech processing, but little is known about children's use of this information during online word recognition. In two eye-tracking experiments, we investigate 2-year-olds' sensitivity to a specific type of subphonemic detail: coarticulatory mismatch. In Experiment 1, toddlers viewed images of familiar objects (e.g., a boat and a book) while hearing labels containing appropriate or inappropriate coarticulation. Inappropriate coar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…Results showed that participants fixated faster on the target image when the recording contained assimilated nasal consonants, suggesting that participants used their knowledge of this process to anticipate the identity of an upcoming consonant. Similar effects have been found for other cues as well, including vowel formant transitions (Dahan et al 2001;Salverda et al 2014;Mahr et al 2015;Paquette-Smith et al 2016), vowel nasalization (Beddor et al 2013;Paquette-Smith et al 2016;Zamuner et al 2016, Desmeules-Trudel andZamuner 2019), and segment duration (Salverda et al 2003;Blazej and Cohen-Goldberg 2015).…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Results showed that participants fixated faster on the target image when the recording contained assimilated nasal consonants, suggesting that participants used their knowledge of this process to anticipate the identity of an upcoming consonant. Similar effects have been found for other cues as well, including vowel formant transitions (Dahan et al 2001;Salverda et al 2014;Mahr et al 2015;Paquette-Smith et al 2016), vowel nasalization (Beddor et al 2013;Paquette-Smith et al 2016;Zamuner et al 2016, Desmeules-Trudel andZamuner 2019), and segment duration (Salverda et al 2003;Blazej and Cohen-Goldberg 2015).…”
Section: Introductionsupporting
confidence: 74%
“…The long-distance nature of sibilant harmony and other types of consonant harmony is of particular interest when we consider its potential to facilitate language processing. A growing body of research has demonstrated that during spoken word recognition, listeners can use a variety of cues to anticipate an upcoming sound before it is realized (Dahan et al 2001;Salverda et al 2003Salverda et al , 2014Gow and McMurray 2007;Beddor et al 2013;Mahr et al 2015;Blazej and Cohen-Goldberg 2015;Paquette-Smith et al 2016;Zamuner et al 2016, Desmeules-Trudel andZamuner 2019). This literature, however, has focused on local dependencies between adjacent segments, as opposed to long-distance phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the phonetic transcriptions (reported in Appendix A) indicate that the Australian accent deviated from Canadian English on more of the target words compared to the Mandarin-accented English speaker. That being said, phonetic transcriptions do not fully capture pronunciation differences between accents, and we know young children are sensitive to sub-phonemic differences in the pronunciation of speech sounds (Paquette-Smith, Fecher & Johnson, 2016). Moreover, the results of Experiment 3 do not support the notion that the Mandarin speaker was easier to comprehend.…”
Section: Discussionmentioning
confidence: 78%
“…Coarticulation processing in adults and children Coarticulation and phonetic variability impact spoken word recognition in adults (Archibald & Joanisse, 2011;Beddor, McGowan, Boland, Coetzee & Basher, 2013;Dahan, Magnuson, Tanenhaus & Hogan, 2001;Desmeules-Trudel & Zamuner, 2019;Gow, 2003;McMurray, Clayards, Tanenhaus & Aslin, 2008;McMurray, Tanenhaus & Aslin, 2002;Salverda, Kleinschmidt & Tanenhaus, 2014) and children (Cross & Joanisse, 2018;Johnson & Jusczyk, 2001;Mahr, McMillan, Saffran, Weismer & Edwards, 2015;Paquette-Smith, Fecher & Johnson, 2016;Zamuner, Moore & Desmeules-Trudel, 2016). One coarticulatory phenomenon that influences auditory word recognition in monolingual English-speaking adults and young children is vowel nasalization (Beddor et al, 2013;Zamuner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to bilingual children's perception of phonetic properties that are present in both of their languages (e.g., vowel nasalization for English–French bilinguals, however with different phonological status in their languages), little is known concerning the perception of sublexical (e.g., coarticulatory) information. However, we know that young monolingual children's word recognition patterns are significantly influenced by coarticulation (Paquette-Smith et al, 2016; Zamuner et al, 2016) and bilingual children can maintain sensitivity to phonetic properties in more than one language (Burns et al, 2007; Kuhl et al, 2008; Ramon-Casas et al, 2017; Sundara et al, 2006).…”
Section: Introductionmentioning
confidence: 99%